Molecular characterization of vancomycin-resistant Enterococcus faecium and identification of a clinical strain co-harboring the G2505A mutation associated with linezolid resistance from a tertiary hospital in China - Ni Suo; Yujing Wang; Chunguang Chen; Haijun Li; Nan Yi; Xiaogai Li; Cailin Liu; Wanhai Wang (Microbiology Spectrum, 2026)
ABSTRACT The rise of vancomycin-resistant Enterococcus faecium (VREfm) poses a growing global health threat. This study aimed to characterize the molecular features and resistance mechanisms of clinical VREfm isolates from a Chinese tertiary hospital. Eighteen VREfm isolates were identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and whole-genome sequencing (WGS). Antimicrobial susceptibility testing was performed via the broth microdilution method. Resistance mechanisms and molecular epidemiology were analyzed using WGS and bioinformatics tools. Additionally, plasmid-mediated transfer of vancomycin resistance genes was evaluated through conjugation assays. Among the 18 VREfm isolates, 13 carried only the vanHAX gene cluster, while 5 harbored both the vanHAX and vanHMX gene clusters. Notably, two VREfm strains—EFM250320 and EFM250826—were isolated from the same patient but from specimens of the same type collected at different time points. Strain EFM250320 carried both the vanHAX and vanHMX gene clusters, whereas strain EFM250826 carried not only the vanHAX and vanHMX gene clusters, but also a G2505A mutation in the 23S rRNA gene associated with linezolid resistance. Five distinct sequence types (STs) were identified, with ST80 (44.4%, 8/18) being the predominant type. IMPORTANCE This study reveals notable drug resistance patterns in vancomycin-resistant Enterococcus faecium (VREfm) bacteria at our hospital, with multiple resistance genes identified in the isolates. Notably, one strain was found to concurrently harbor both the vanHAX and vanHMX gene clusters, along with a G2505A mutation in the 23S rRNA gene that confers resistance to linezolid. The dissemination of the dominant ST80 clone suggests potential intra-hospital transmission. These findings underscore the necessity for enhanced surveillance and stringent infection control measures to curb the spread of such hazardous multidrug-resistant pathogens.